(3Hjf GdfXQjI hGdJWHjbs - (3RcQjG CMeO(B, (3YRGes ((3YeGf(B:s (3OGQ GdeSjQI ddfTQ hGdJhRjY hGdWHGYI(B,s, 2022)
(3eaghe GdJShjb, eaGgje GdJShjb GdLhgQjI(B/ (3GdCSGSjI, eQGMd JWhQ GdJShjb, XGgQI bUQ GdfXQ GdJShjbj, GdaQU GdJShjbjI hGNJjGQ GdeRjL GdJShjbj, CSHGH GdEgJeGe HGdJShjb, hXGFa GdJShjb, GdefGaY GdJj jDOjgG GdJShjb, GdGfJbGOGJ GdJj hLgJ dYde GdJShjb, GdHjFI GdJShjbjI, JYQja GdHjFI GdJShjbjI, YhGed GdHjFI GdJShjbjI, JLRFI (B/ (3JbSje GdShb, GdShb, GdGSJQGJjLjI GdJShjbjI, GSJQGJjLjI JLRFI (B/ (3JbSje GdShb, TQhW GdJLRFI GdaYGdI ddShb, eYGjjQ GdGNJjGQ Hjf GSJQGJjLjGJ JLRFI (B/ (3JbSje GdShb, CSS JbSje GdCShGb, Sdhc GdeSJgdc, CShGb GdeSJgdc, CfhGY GdSdhc GdTQGFj ddeSJgdc GdfgGFj, COhGQ GdSdhc GdTQGFj, eQGMd YedjI GJNGP GdeSJgdc dbQGQ GdTQGA, fehPL GdSdhc GdTQGFj, GdYhGed GdeDKQI aj GdSdhc GdGSJgdGcj, GdeYdheGJ hGdHMhK GdJShjbjI, fXGe GdeYdheGJ GdJShjbj, NWhGJ GdHMK GdJShjbj, SjGSGJ hbQGQGJ GdefJLGJ, JYQja GdSdY, JUfja GdSdY, OhQI MjGI GdSdY, GdYdGeI GdJLGQjI, GdJZdja hGdYHhGJ, JWhjQ GdfJLGJ GdLOjOI, JYQja GdSdYI GdLOjOI, CSHGH JWhjQ GdSdY GdLOjOI, eQGMd JWhjQ GdSdY GdLOjOI, CSGH fLGM GdSdY GdLOjOI, CSHGH aTd GdSdY GdLOjOI, JShjb GdNOeGJ, JYQja GdNOeI, JUfja GdNOeGJ, NUGFU GdNOeGJ, CgejI GdNOeGJ, GdeVGejf GdJShjbjI GdNOeGJ, GdJSYjQ, eaghe GdJSYjQ, GUWdGMGJ CNQi ddSYQ, GdCgejI GdeJRGjOI ddSYQ, NWhGJ YedjI GdJSYjQ, GdJhRjY, JYQjag, hXGFa bfhGJ GdJhRjY, CgejI bfhGJ GdJhRjY, CfhGY bfhGJ GdJhRjY, JLGQI GdJLRFI, eJGLQ GdLedI, GdhSWGA GdhXjajhf, GdHjY GdeHGTQ, NWhGJ JUeje hGNJjGQ GdbfGI GdJhRjYjI GdefGSHI, OjfGejcjI bfhGJ GdJhRjY, GdJQhjL, eagheg hCgOGag, CgOGa GdJQhjL cfTGW JShjbj, GdYhGed GdeDKQI aj GdeRjL GdJQhjLj, YfGUQ GdeRjL GdJQhjLj, JfTjW GdeHjYGJ, GdHjY GdTNUj, eQGMd YedjI GdHjY GdTNUj, EOGQI GdHjY GdTNUj, GdYdGbGJ GdYGeI,GdJShjb GdEdcJQhfj hGdJLGQI GdEdcJQhfjI, eGgjI THcI GdeYdheGJ GdSQjYI (B((3GdGfJQfJ(B)(3, eGgjI GdTHcI GdYfcHhJjI GdOhdjI, CfXeI GdeYdheGJ eGHjf GdeDSSGJ aj GdJLGQI GdEdcJQhfjI, GdWHjYI GdYdejI ddJLGQI GdEdcJQhfjI, GdJShjb GdEdcJQhfj(B.s
(3GdeQGLY U(B.65(3, (B94(3, (B126(3, (B154(3, (B175(3, (B223(3, (B278(3, (B313(3, (B355(3, (B433(3, (B461.s
Keywords: (3GdCShGbs; (3GdESJgdGcs; (3GdJShjbs